Phase I: sustainable integrated management of whitefly as pests and vectors of plant viruses in the tropics: a system-wide IPM initiative project - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1996)
In the past decade, whiteflies (Homoptera:Aleyrodidae), as pests and vectors of plant viruses, have become one of the most serious crop protection problems in the tropics. The result has been devastating crop losses for small-holder producers and unprecedented insecticide abuse. There is urgent need to develop IPM systems that would reduce insecticide use and help reestablish the ecological equilibrium by means of non-chemical approaches to whitefly control, such as biological and microbial control, or crop varieties with increased resistance to whiteflies (WFs) and whitefly-transmitted viruses (WTVs). One of the principle obstacles to achieving IPM solutions has been the isolated and uncoordinated fashion in which researchers have been working. The Whitefly IPM Project proposes to organize a network for researchers in the tropics who are working on whiteflies and whitefly-transmitted viruses; promote the standardization of research methodologies among researchers; and facilitate the collecting of critical, missing data in order to adapt, develop and implement effective IPM packages for whitefly and virus management